An Output Capacitor-Less Low-Dropout Regulator with 0–100 mA Wide Load Current Range - Jihoon Park; Woong-Joon Ko; Dong-Seok Kang; Yoonmyung Lee; Jung-Hoon Chun (Energies, 2019)
An output capacitor-less low-dropout (OCL-LDO) regulator with a wide range of load currents is proposed in this study. The structure of the proposed regulator is based on the flipped-voltage-follower LDO regulator. The feedback loop of the proposed regulator consists of two stages. The second stage is turned on or off depending on the variation in the output load current. Hence, the regulator can retain a phase margin at a wide range of load currents. The proposed regulator exhibits a better regulation performance compared to the ones in previous studies. The test chip is fabricated using a 65-nm CMOS process.